Mapping global urban inequality under climate change and its interaction with sustainable development - Yinshuai Li; Nan Jia; Zhan Zhang; Jie Cheng; Wen Song; Lingbo Liu; Shuming Bao; Lilin Zheng; Ruishan Chen (GIScience & Remote Sensing)
Global cities are significantly affected by climate change, leading to increased inequality and further vulnerability among marginalized groups. To understand the impacts and challenges of climate change on urban inequality and enable long-term dynamic monitoring, we established an open-source, replicable, and visually-based bibliometric analysis workflow on the KNIME platform. Meanwhile, the systematic literature review was achieved by adding a meta-analysis. On this basis, we evaluated urban inequality in global countries from 2000 to 2021, exploring whether academic attention (represented by the number of published articles) is balanced with actual climate vulnerability and urban inequality. Finally, through Spearman correlation and network analysis methods, we also revealed how urban inequalities affect and constrain the achievement of the Sustainable Development Goals (SDGs). The results indicate that the United States, China, and India were early to pay attention to urban inequality under climate change and contributed a large number of published articles. The research themes can be categorized into 10 parts, including climate, cultural, and economic inequality. From 2000 to 2021, the overall trend of urban inequality in global countries decreased, with average and median scores gradually decreasing from 0.44 and 0.46 to 0.43. Additionally, there is an imbalance between actual climate vulnerability, urban inequality, and academic attention. Most countries in Africa, South America, South Asia, and the Middle East urgently need academic assistance and technical support. Except for SDG12 (Responsible consumption and production) and SDG13 (Climate action), most types of urban inequalities will hinder the performance of SDGs, with a negative correlation. Cultural, human, and health inequalities, as well as SDG12, SDG13, SDG11 (Sustainable cities and communities), and SDG16 (Peace, justice, and strong institutions) have become key nodes in the correlation network for synergistically advancing urban equity and sustainable development. Simultaneously, differentiated strategies should be adopted: countries with highly interconnected networks such as high-income countries should pursue integrated policy coordination, while those with strongly modular networks such as high climate vulnerable countries should adopt localized solutions and strengthen cross-module collaboration. Our study can provide a scientific basis for formulating targeted policies and intervention measures to address urban inequality under the long-term disruptions of climate change, thereby promoting the sustainable development of cities, as well as social equity and justice.